KEPUASAN PELANGGAN YANG DIPENGARUHI OLEH TARIF DAN KUALITAS PELAYANAN PADA PANGKAS RAMBUT SEROJA BANGKINANG KOTA - Azhari, Azhari; Zulher, Zulher; Bahri, Syamsul; Hidayat, Taufik (Ensiklopedia of Journal, 2024)
This research aims to determine the effect of rates and service quality simultaneously and partially on customer satisfaction at Seroja Bangkinang barbershop with a sample size of 98 respondents taken using the Slovin formula and analyzed using multiple linear analysis. Hypothesis testing is carried out by simultaneous testing and partial testing. Based on the research results, it can be concluded that rates and service quality simultaneously have a positive and significant effect on customer satisfaction. Likewise, partial test results show that rates and service quality have an effect on customer satisfaction at Seroja Bangkinang barbershop. The close relationship between the independent variable and the dependent variable is very strong with the contribution of the independent variable to the dependent variable being 76.30%.